EVALUATING THE COST-EFFECTIVENESS OF AMLODIPINE WITH ATENOLOL VERSUS AMLODIPINE WITH TELMISARTAN IN A RURAL COMMUNITY HEALTH CENTER, ANDHRAPRADESH - SATHYAMURTHY, SEELISETTY; BHARATHI, U.; KUMAR, M. AMRUTH KIRAN (International Journal of Current Pharmaceutical Research, 2026)
Objective: The objective of this study was to compare the cost-effectiveness of two antihypertensive combinations, Amlodipine with Atenolol and Amlodipine with Telmisartan, among hypertensive patients attending a rural community health centre in Andhra Pradesh. The study aimed to evaluate the economic efficiency of these regimens in relation to their clinical outcomes. Specific objectives included assessing the clinical effectiveness of both combinations in controlling systolic and diastolic blood pressure and determining their respective cost-effectiveness ratios for the target population. The findings were intended to identify a clinically effective and economically sustainable antihypertensive therapy suitable for resource-limited rural healthcare settings. Methods: A prospective observational study was conducted over two months among 106 hypertensive patients, divided equally into two treatment groups (n1 = 53; n2 = 53). Blood pressure measurements were recorded at baseline and during two follow-up visits at one-month intervals. Drug costs were obtained from the hospital pharmacy index. Clinical effectiveness was assessed through reductions in systolic and diastolic blood pressure, and pharmacoeconomic evaluation was performed using cost-effectiveness ratios and incremental cost-effectiveness ratio (ICER). Results: Both combinations produced significant reductions in systolic blood pressure readings (p<0.05) mean diastolic blood pressure reduction was almost similar in both groups, while mean systolicblood pressure reduction was significant. Pricing analysis showed substantially lower costs for the Amlodipine+Atenolol regimen. Cost-effectiveness analysis revealed more favourable outcomes for Amlodipine+Atenolol (C/E = 1.24) compared with Amlodipine+Telmisartan (C/E = 1.86). The ICER value (8.26) indicated that the Telmisartan combination provided minimal additional benefit at a significantly higher cost. Conclusion: Although both regimens effectively lowered blood pressure, Amlodipine+Atenolol demonstrated markedly superior cost-effectiveness. This combination represents a more affordable and sustainable option for hypertension management in rural primary care settings, supporting its preferential use in resource-limited populations.